Report of the Committee on Integrated Coal Policy - Planning Commission (Planning Commission, 1996)
The Committee on Integrated Coal Policy was set up under Planning Commission’s notification dated 27 April 1995 with comprehensive Terms of Reference. Coal being considered the most important source of commercial energy in India, subserving the interests of Power, Steel and a host of other industries of importance for the country’s economic growth, it was understandable that the Government, having initiated a new Economic and Liberalisation Policy, desired to be advised on the formulation of an integrated policy that would keep in view the country’s interests in the next decade.
Planning Commission, Government of India